Accurate dark-matter halo elongation from weak-lensing stacking analysis. Issue 4 (22nd October 2022) - Gonzalez, Elizabeth J; Hoffmann, Kai; Gaztañaga, Enrique; García Lambas, Diego R; Fosalba, Pablo; Crocce, Martin; Castander, Francisco J; Makler, Martín
ABSTRACT: Shape estimates that quantifying the halo anisotropic mass distribution are valuable parameters that provide information on their assembly process and evolution. Measurements of the mean shape estimates for a sample of cluster-sized haloes can be used to test halo formation scenarios, as well as improving the modelling of potential biases in constraining cosmological parameters using these systems. In this work, we test the recovery of halo cluster shapes and masses applying weak-lensing stacking techniques. To this end, we use lensing shear and a new dark-matter halo catalogue, derived from the light-cone output of the cosmological simulation MICE-GC. We perform this study by combining the lensing signals obtained for several samples of haloes, selected according to their mass and redshift, taking into account the main directions of the dark-matter distributions. In the analysis, we test the impact of several potential introduced systematics, such as the adopted modelling, the contribution of the neighbouring mass distribution, miscentring, and misalignment effects. Our results show that when some considerations regarding the halo relaxation state are taken into account, the lensing semi-axial ratio estimates are in agreement within a 5 per cent with the mean shapes of the projected dark-matter particle distribution of the stacked haloes. The presented methodology provides a useful tool to derive reliable shapes of galaxy clusters and to contrast them with those expected from numerical simulations. Furthermore, our proposed modelling, that takes into account the contribution of neighbouring haloes, allows to constraint the elongation of the surrounding mass distribution.